A method for preparing low-content carbon fiber brake pad
By using superdispersant in carbon fiber brake pads to improve material interactions, the problem of insufficient performance of existing brake pads is solved, and a more uniform composite material and higher performance performance is achieved.
Patent Information
- Application Number
- CN202411137333.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-08-19
AI Technical Summary
The existing carbon fiber brake pads have problems such as poor braking effect, poor resistance to external impact, and poor friction and wear performance.
The preparation method of low-content carbon fiber brake pads is adopted to improve the interaction between fibers, phenolic resins and inorganic fillers through superdispersant, reduce the tendency of aggregation, and improve the dispersion of the mixture and the interface bonding strength.
It significantly improves the uniformity of brake pad composite materials, improves the overall quality and performance of the product, and enhances friction and mechanical properties.
Smart Images

Figure C5UC64LSVCKFPU3JGAMSX2L7RJFKH4YXZ3E735X2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brake pad preparation, in particular to a method for preparing a low-content carbon fiber brake pad. Background Art
[0002] Carbon fiber is a new type of high molecular inorganic fiber material with good mechanical and chemical properties such as low density, high strength, wear resistance, high temperature resistance, stable chemical properties, and wear resistance. It can conduct electricity and heat, and has attenuation characteristics under high vibration conditions. It has a relatively low thermal expansion coefficient and can shield electromagnetic signals. Because of such diverse and excellent performance, carbon fiber can be used in many fields such as aviation, rail, vehicle applications, and people's livelihood products.
[0003] Chinese patent CN111425541A: relates to the technical field of vehicle braking devices, specifically, to a carbon fiber brake pad and its preparation method. It is prepared from an adhesive, reinforcing fiber, a friction performance regulator and a filler; wherein the adhesive includes resin and rubber powder; the reinforcing fiber includes carbon fiber, aramid fiber, potassium magnesium titanate; the friction performance regulator includes graphite, chromite powder, zircon powder, antimony sulfide, molybdenum disulfide, tin sulfide, aluminum oxide; the filler is barium sulfate.
[0004] Chinese patent CN105156526A: provides a method for preparing a carbon fiber brake pad composite material, first taking ethylene bis stearamide, heating to 150-170°C, adding carbon fiber, stirring, cooling, adding polyethylene imine, glycerol, dimethylaminoethyl methacrylate, lecithin, epoxy resin, heating and heat preservation, stirring, cooling to room temperature, and obtaining modified carbon fiber; then taking sodium stearoyl lactylate, olefin amide, ammonium persulfate, paraffin, silicon dioxide, heating and heat preservation, stirring, cooling to room temperature, and obtaining mixture A; then mixing the modified carbon fiber and mixture A, drying, and ball milling to obtain mixture B; finally, mixing the obtained mixture with graphite powder, titanium oxide powder, iron powder, nickel powder, methyl silicone oil, and polycarbonate, and sintering in a vacuum sintering furnace to obtain.
[0005] Chinese Patent CN102206482A: A method for preparing a carbon fiber brake pad. The invention relates to the technical field of automobile brake systems. Aiming at the problems of thermal conductivity and high temperature controllability of the current non-asbestos organic (NAO) automobile brake pads, the invention proposes a method for preparing a carbon fiber brake pad. The carbon fiber brake pad is prepared from the following raw materials, and the weight percentage of each component of the carbon fiber raw material is: carbon fiber 35-55%, phenolic resin 15-35%, and powder filler 20-40%.
[0006] The brake pads prepared according to the above-mentioned public technical data have the technical problems of poor braking effect, poor strength to resist external impact, and unsatisfactory friction and wear performance. Summary of the invention
[0007] In view of one or more technical problems existing in the prior art, the present invention provides a method for preparing a low-content carbon fiber brake pad. The superdispersant of the present invention can improve the interaction between the fiber, phenolic resin and inorganic filler due to its special structure and functional groups, and reduce the aggregation tendency, thereby significantly improving the dispersion of the mixture; this ensures the uniformity of the brake pad composite material and improves the overall quality and performance of the product.
[0008] The technical solution of the present invention:
[0009] A method for preparing a low-content carbon fiber brake pad, the operating steps of which are:
[0010] S1: Weigh 1-5 parts of pretreated carbon fiber, 5-10 parts of phenolic resin, 10-20 parts of mineral fiber, 0.05-0.5 parts of hyperdispersant, 5-10 parts of flake graphite, 1-5 parts of alumina, 15-20 parts of calcium carbonate, and 30-40 parts of filler by weight, and stir and mix for 10-15 minutes;
[0011] S2: The mixed material is placed in a special hot press, hot-pressed into shape, and then heat-treated and mechanically processed to obtain a low-content carbon fiber brake pad.
[0012] It is further specified that the mineral fiber is one of sepiolite fiber, basalt fiber and wollastonite fiber.
[0013] It is further defined that the filler is one of vermiculite, barium sulfate, barite, sepiolite and talc.
[0014] It is further defined that the specific steps of synthesizing the hyperdispersant are:
[0015] T1: 0.06-0.9 parts of diallyl bisphenol A, 0.05-0.5 parts of diallyl selenium, 3-7 parts of dilithium mercaptosuccinate, 30-50 parts of ethanol, and 2-5 parts of sodium ethoxide are added into a closed reactor, nitrogen is introduced, and the reaction is carried out at 70-80°C for 100-200 minutes under nitrogen protection;
[0016] T2: Add 50-80 parts of polyether F127 diacrylate, react at 60-70°C for 1-3 hours under nitrogen protection; remove ethanol by vacuum distillation to obtain a super dispersant.
[0017] It is further defined that the average molecular weight of the polyether F127 diacrylate is 10,000-13,000.
[0018] It is further defined that the hot pressing pressure is 30-45 MPa, the temperature is 150-160° C., and the time is 20-30 min.
[0019] It is further defined that the heat treatment steps are: firstly heating to 130-140°C and treating for 40-60 minutes; then heating to 150-160°C and treating for 150-180 minutes; finally heating to 170-180°C and treating for 4-6 hours.
[0020] Further defined, the steps of carbon fiber pretreatment are:
[0021] A1: Place the carbon fiber in anhydrous ethanol, soak for 5-8 hours, then place it in a 5-10% hydrogen peroxide solution, and continue soaking for 20-40 minutes;
[0022] A2: Rinse the soaked carbon fiber with distilled water for 10-20 times and dry it to obtain pretreated carbon fiber.
[0023] It is further defined that the carbon fiber is chopped carbon fiber with a length of 3-6 mm.
[0024] It is further defined that the drying temperature is 80-100° C. and the drying time is 30-50 minutes.
[0025] Reaction mechanism
[0026] 1. Mechanism of step T1:
[0027] Diallyl bisphenol A and diallyl selenium contain active double bonds that can react with the thiol group in dilithium mercaptosuccinate; it is carried out through a thiol-ene click chemistry reaction, in which the thiol group is added to the carbon-carbon double bond to form a thioether link; sodium ethoxide, as an alkaline catalyst, helps to promote the addition reaction of the thiol to the double bond, thereby improving the reaction efficiency; the intermediate product formed in this step is a functional molecule, whose structure contains active thiol groups and lithium carboxylate groups, which provides the possibility for the next reaction.
[0028] 2. Mechanism of step T2:
[0029] The addition of polyether F127 diacrylate introduces additional double bonds, which can further react with the thiol groups from the first step to form a highly cross-linked structure through thiol-ene click chemistry; this cross-linking can enhance the mechanical properties of the material at the molecular level and improve its thermal stability and chemical resistance; the final product obtained after removing ethanol by reduced pressure distillation is a highly functional hyperdispersant with polysulfide bonds and possible carboxylate links.
[0030] Technical Effects
[0031] The present invention provides a method for preparing a low-content carbon fiber brake pad. Compared with the prior art, the present invention has the following significant effects:
[0032] 1. Improved dispersion:
[0033] Due to its special structure and functional groups, the hyperdispersant can improve the interaction between fibers, phenolic resins and inorganic fillers, reduce the tendency to aggregate, and thus significantly improve the dispersion of the mixture; this ensures the uniformity of the brake pad composite material and improves the overall quality and performance of the product.
[0034] 2. Increased interface bonding strength:
[0035] The polysulfide bonds and carboxylate links in the hyperdispersant can form strong chemical bonds or strong physical interactions with phenolic resin and other components to enhance interfacial adhesion; such chemical and physical effects are conducive to stress transfer and can better withstand high pressure and temperature when the brake pad is in use. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0037] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0038] Among them, the impact strength and friction performance tests in the specific implementation plan are tested with reference to GB5763-2008.
[0039] Example 1
[0040] A method for preparing a low-content carbon fiber brake pad, the operating steps of which are:
[0041] S1: Weigh 1g of pretreated carbon fiber, 5g of phenolic resin, 10g of mineral fiber, 0.05g of hyperdispersant, 5g of flake graphite, 1g of alumina, 15g of calcium carbonate, and 30g of filler, and stir and mix for 10min;
[0042] S2: The mixed material is placed in a special hot press, hot-pressed into shape, and then heat-treated and mechanically processed to obtain a low-content carbon fiber brake pad.
[0043] The mineral fiber is sepiolite fiber.
[0044] The filler is vermiculite.
[0045] The specific steps of synthesizing the hyperdispersant are:
[0046] T1: 0.06 g of diallyl bisphenol A, 0.05 g of diallyl selenium, 3 g of dilithium mercaptosuccinate, 30 g of ethanol, and 2 g of sodium ethoxide were added into a closed reactor, nitrogen was introduced, and the mixture was reacted at 70° C. for 100 minutes under nitrogen protection;
[0047] T2: Add 50 g of polyether F127 diacrylate, react at 60° C. for 1 h under nitrogen protection, and remove ethanol by vacuum distillation to obtain a hyperdispersant.
[0048] The average molecular weight of the polyether F127 diacrylate is 10,000.
[0049] The hot pressing pressure is 30 MPa, the temperature is 150° C., and the time is 20 min.
[0050] The heat treatment steps are: firstly heating to 130°C and treating for 40 minutes; then heating to 150°C and treating for 150 minutes; and finally heating to 170°C and treating for 4 hours.
[0051] The steps of carbon fiber pretreatment are:
[0052] A1: Place the carbon fiber in anhydrous ethanol, soak for 5 hours, then place it in a 5% hydrogen peroxide solution and continue soaking for 20 minutes;
[0053] A2: The soaked carbon fiber is rinsed with distilled water for 10 times and dried to obtain pretreated carbon fiber.
[0054] The carbon fiber is chopped carbon fiber with a length of 3 mm.
[0055] The drying temperature is 80° C. and the drying time is 30 minutes.
[0056] Example 2
[0057] A method for preparing a low-content carbon fiber brake pad, the operating steps of which are:
[0058] S1: Weigh 2 g of pretreated carbon fiber, 6 g of phenolic resin, 13 g of mineral fiber, 0.2 g of hyperdispersant, 6 g of flake graphite, 2 g of alumina, 16 g of calcium carbonate, and 33 g of filler, and stir and mix for 12 min;
[0059] S2: The mixed material is placed in a special hot press, hot-pressed into shape, and then heat-treated and mechanically processed to obtain a low-content carbon fiber brake pad.
[0060] The mineral fiber is basalt fiber.
[0061] The filler is barium sulfate.
[0062] The specific steps of synthesizing the hyperdispersant are:
[0063] T1: 0.3 g of diallyl bisphenol A, 0.2 g of diallyl selenium, 4 g of dilithium mercaptosuccinate, 35 g of ethanol, and 3 g of sodium ethoxide were added into a closed reactor, nitrogen was introduced, and the reaction was carried out at 75°C for 140 minutes under nitrogen protection;
[0064] T2: Add 60 g of polyether F127 diacrylate, react at 65° C. for 2 h under nitrogen protection, and remove ethanol by vacuum distillation to obtain a hyperdispersant.
[0065] The average molecular weight of the polyether F127 diacrylate is 11,000.
[0066] The hot pressing pressure is 35 MPa, the temperature is 155° C., and the time is 25 min.
[0067] The heat treatment steps are: firstly heating to 135°C and treating for 45 minutes; then heating to 155°C and treating for 160 minutes; and finally heating to 175°C and treating for 5 hours.
[0068] The steps of carbon fiber pretreatment are:
[0069] A1: Place the carbon fiber in anhydrous ethanol, soak for 6 hours, then place it in a 6% hydrogen peroxide solution and continue soaking for 25 minutes;
[0070] A2: The soaked carbon fiber is rinsed with distilled water for 14 times and dried to obtain pretreated carbon fiber.
[0071] The carbon fiber is chopped carbon fiber with a length of 4 mm.
[0072] The drying temperature is 85° C. and the drying time is 35 minutes.
[0073] Example 3
[0074] A method for preparing a low-content carbon fiber brake pad, the operating steps of which are:
[0075] S1: Weigh 4 g of pretreated carbon fiber, 8 g of phenolic resin, 18 g of mineral fiber, 0.4 g of hyperdispersant, 8 g of flake graphite, 4 g of alumina, 18 g of calcium carbonate, and 38 g of filler, and stir and mix for 14 min;
[0076] S2: The mixed material is placed in a special hot press, hot-pressed into shape, and then heat-treated and mechanically processed to obtain a low-content carbon fiber brake pad.
[0077] The mineral fiber is basalt fiber.
[0078] The filler is barite.
[0079] The specific steps of synthesizing the hyperdispersant are:
[0080] T1: 0.6 g of diallyl bisphenol A, 0.4 g of diallyl selenium, 6 g of dilithium mercaptosuccinate, 45 g of ethanol, and 4 g of sodium ethoxide were added to a closed reactor, nitrogen was introduced, and the reaction was carried out at 75°C for 180 minutes under nitrogen protection;
[0081] T2: Add 70 g of polyether F127 diacrylate, react at 65° C. for 2 h under nitrogen protection, and remove ethanol by vacuum distillation to obtain a hyperdispersant.
[0082] The average molecular weight of the polyether F127 diacrylate is 12,000.
[0083] The hot pressing pressure is 40 MPa, the temperature is 155° C., and the time is 25 min.
[0084] The heat treatment steps are: firstly heating to 135°C and treating for 55 minutes; then heating to 155°C and treating for 170 minutes; and finally heating to 175°C and treating for 5 hours.
[0085] The steps of carbon fiber pretreatment are:
[0086] A1: Place the carbon fiber in anhydrous ethanol, soak for 7 hours, then place it in an 8% hydrogen peroxide solution and continue soaking for 35 minutes;
[0087] A2: The soaked carbon fiber is rinsed with distilled water for 18 times and dried to obtain pretreated carbon fiber.
[0088] The carbon fiber is chopped carbon fiber with a length of 5 mm.
[0089] The drying temperature is 95° C. and the drying time is 45 minutes.
[0090] Example 4
[0091] A method for preparing a low-content carbon fiber brake pad, the operating steps of which are:
[0092] S1: Weigh 5 g of pretreated carbon fiber, 10 g of phenolic resin, 20 g of mineral fiber, 0.5 g of hyperdispersant, 10 g of flake graphite, 5 g of alumina, 20 g of calcium carbonate, and 40 g of filler, and stir and mix for 15 min;
[0093] S2: The mixed material is placed in a special hot press, hot-pressed into shape, and then heat-treated and mechanically processed to obtain a low-content carbon fiber brake pad.
[0094] The mineral fiber is wollastonite fiber.
[0095] The filler is talc.
[0096] The specific steps of synthesizing the hyperdispersant are:
[0097] T1: 0.9 g of diallyl bisphenol A, 0.5 g of diallyl selenium, 7 g of dilithium mercaptosuccinate, 50 g of ethanol, and 5 g of sodium ethoxide were added into a closed reactor, nitrogen was introduced, and the mixture was reacted at 80° C. for 200 minutes under nitrogen protection;
[0098] T2: Add 80 g of polyether F127 diacrylate, react at 70° C. for 3 h under nitrogen protection, and remove ethanol by distillation under reduced pressure to obtain a hyperdispersant.
[0099] The average molecular weight of the polyether F127 diacrylate is 13,000.
[0100] The hot pressing pressure is 45 MPa, the temperature is 160° C., and the time is 30 min.
[0101] The heat treatment steps are: firstly heating to 140°C and treating for 60 minutes; then heating to 160°C and treating for 180 minutes; and finally heating to 180°C and treating for 6 hours.
[0102] The steps of carbon fiber pretreatment are:
[0103] A1: Place the carbon fiber in anhydrous ethanol, soak for 8 hours, then place it in a 10% hydrogen peroxide solution and continue soaking for 40 minutes;
[0104] A2: The soaked carbon fiber is rinsed with distilled water for 20 times and dried to obtain pretreated carbon fiber.
[0105] The carbon fiber is chopped carbon fiber with a length of 6 mm.
[0106] The drying temperature is 100° C. and the drying time is 50 minutes.
[0107] Comparative Example 1
[0108] This example is a comparative example of Example 1, except that no hyperdispersant is added, and the rest is the same as Example 1.
[0109] Comparative Example 2
[0110] This example is a comparative example of Example 1, except that diallyl bisphenol A is not added, and the other conditions are the same as Example 1.
[0111] Comparative Example 3
[0112] This example is a comparative example of Example 1, except that polyether F127 diacrylate is not added, and the other conditions are the same as Example 1.
[0113] Table 1 Test results
[0114]
[0115] Through the data analysis of the above embodiments and comparative examples, the hyperdispersant prepared by the present invention can effectively improve the friction performance and mechanical properties of the brake pad.
[0116] The embodiments of the invention disclosed above are only used to help illustrate the invention. The embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. According to the content of this specification, many modifications and changes can be made. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the invention, so that those skilled in the art can understand and use the invention well.
Claims
1. A method for preparing a low-content carbon fiber brake pad, the operating steps of which are: S1: According to weight, weigh 1-5 parts of pretreated carbon fiber, 5-10 parts of phenolic resin, 10-20 parts of mineral fiber, 0.05-0.5 parts of hyperdispersant, 5-10 parts of flake graphite, 1-5 parts of alumina, 15-20 parts of calcium carbonate, and 30-40 parts of filler. Stir and mix for 10-15 minutes; S2: putting the mixed material into a special hot press, hot pressing and forming, and then heat treating and machining to obtain a low-content carbon fiber brake pad; The specific steps of synthesizing the hyperdispersant are: T1: 0.06-0.9 parts of diallyl bisphenol A, 0.05-0.5 parts of diallyl selenium, 3-7 parts of dilithium mercaptosuccinate, 30-50 parts of ethanol, and 2-5 parts of sodium ethoxide are added into a closed reactor, nitrogen is introduced, and the reaction is carried out at 70-80°C for 100-200 minutes under nitrogen protection; T2: Add 50-80 parts of polyether F127 diacrylate, react at 60-70°C for 1-3 hours under nitrogen protection; remove ethanol by vacuum distillation to obtain a super dispersant.
2. The method for preparing a low-content carbon fiber brake pad according to claim 1, characterized in that: The mineral fiber is one of sepiolite fiber, basalt fiber and wollastonite fiber.
3. The method for preparing a low-content carbon fiber brake pad according to claim 1, characterized in that: The filler is one of vermiculite, barium sulfate, barite, sepiolite and talc.
4. The method for preparing a low-content carbon fiber brake pad according to claim 1, characterized in that: The average molecular weight of the polyether F127 diacrylate is 10000-13000.
5. The method for preparing a low-content carbon fiber brake pad according to claim 1, characterized in that: The hot pressing pressure is 30-45 MPa, the temperature is 150-160° C., and the time is 20-30 min.
6. The method for preparing a low-content carbon fiber brake pad according to claim 1, characterized in that: The heat treatment steps are: firstly heating to 130-140°C and treating for 40-60min; then heating to 150-160°C and treating for 150-180min; finally heating to 170-180°C and treating for 4-6h.
7. The method for preparing a low-content carbon fiber brake pad according to claim 1, characterized in that: The steps of carbon fiber pretreatment are: A1: Place the carbon fiber in anhydrous ethanol, soak for 5-8 hours, then place it in a 5-10% hydrogen peroxide solution, and continue soaking for 20-40 minutes; A2: Rinse the soaked carbon fiber with distilled water for 10-20 times and dry it to obtain pretreated carbon fiber.
8. The method for preparing a low-content carbon fiber brake pad according to claim 7, characterized in that: The carbon fiber is chopped carbon fiber with a length of 3-6 mm.
9. The method for preparing a low-content carbon fiber brake pad according to claim 7, characterized in that: The drying temperature is 80-100° C. and the drying time is 30-50 minutes.
Citation Information
Patent Citations
Preparation method of carbon fiber brake block
CN102206482A
Preparing method for carbon fiber brake pad composite materials
CN105156526A
Carbon fiber brake pad and manufacturing method thereof
CN111425541A
Drum-type brake pad friction material with high impact strength
CN104877631A
Synthetic method of hyperbranched methacrylate
CN115232311A